Multicenter Study of Age, Frailty, and Waitlist Mortality Among Liver Transplant Candidates. Issue 6 (June 2020) - Haugen, Christine E.; McAdams-DeMarco, Mara; Holscher, Courtenay M.; Ying, Hao; Gurakar, Ahmet O.; Garonzik-Wang, Jacqueline; Cameron, Andrew M.; Segev, Dorry L.; Lai, Jennifer C.
Abstract : Objective: To determine if the association of frailty and waitlist mortality varies by candidate age. Background: Frailty, a construct developed in geriatrics, is a state of decreased physiologic reserve, and is associated with mortality while awaiting liver transplantation (LT). However, older candidates have high comorbidity burden and less physiologic reserve, so the relationship between frailty and waitlist mortality may vary by candidate age. Methods: We studied adults listed for LT at 2 transplant centers. The liver frailty index (grip strength, chair stands, balance) was measured at evaluation, with frailty defined as liver frailty index  ≥ 4.5. We compared the prevalence of frailty in older (≥65 yr) and younger (18–64 yr) candidates. We studied the association between frailty, age, interaction between the 2, and waitlist mortality using competing risks regression adjusted for sex, BMI, and MELDNa. Results: Among 882 LT candidates, 16.6% were ≥ 65 years. Older candidates were more likely to be frail (33.3% vs 21.7%, P = 0.002). Older age [adjusted subhazard ratio (aSHR): 2.16, 95% CI: 1.51–3.09, P < 0.001] and frailty (aSHR: 1.92, 95% CI: 1.38–2.67, P < 0.001) were independently associated with higher risk of waitlist mortality. However, the association between waitlist mortality and frailty did not vary by candidate age (aSHR of frailty for younger patients: 1.90, 95% CI: 1.28–2.80, P = 0.001; aSHR of frailty for older patients: 1.98, 95% CI: 1.07–3.67, P = 0.03; P interaction = 0.9). Conclusions: Older candidates experienced higher rates of frailty than younger candidates. However, regardless of age, frailty was associated with nearly 2-fold increased risk of waitlist mortality. Our data support the applicability of the frailty concept to the whole LT population and can guide the development of prehabilitation programs targeting frailty in LT patients of all ages.